Ab initio investigations on the interaction of CO2 and non-metallic superalkalis: structure, stability and electronic properties. (19th March 2021) - Kumar, Ratnesh; Kumar, Abhishek; Srivastava, Ambrish Kumar; Misra, Neeraj
Abstract : Superalkalis are hypervalent species, having lower ionisation energy than alkalis and its strong reducing capabilities can be used in the design of a variety of charge-transfer compounds. The interaction of non-metallic superalkalis such as F2 H3, O2 H5, and N2 H7 with CO2 has been systematically explored using ab initio MP2/6-311++G(d, p) method. We have studied the structural isomers of the resulting superalkali-CO2 complexes and their relative stabilities. We have analyzed their partial charge, spin density, and singly-occupied molecular orbitals' energy, which reveal the relative strength and charge transfer due to the interaction of CO2 with superalkalis. We notice that this interaction leads to the reduction of CO2, as the structure of CO2 moiety in superalkali-CO2 complexes is bent due to electron transfer from superalkalis. Thus, this study should provide some interesting results on the single-electron reduction of CO2 by non-metallic compounds. GRAPHICAL ABSTRACT: